IMPLEMENTING THE PRINCIPLE OF ABUSE OF AUTHORITY PERSPECTIVE IN EXECUTING SUPERIOR ORDERS AGAINST LOCAL GOVERNMENTS - Nathasya Berlian; Belyana Vega F. R. (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
The application of the principle of abuse of authority in the execution of superior orders by local governments is a crucial aspect of good governance. In many countries, local governments are required to follow orders from higher authorities, such as central governments or regional administrations. However, there are instances where local officials abuse their power or exceed their authority while carrying out these orders. This paper aims to explore how the principle of abuse of authority can be implemented in the context of complying with superior orders. The article applies the juridical-normative approach method by reviewing the law on the general principles of good governance, as well as using various legal literature such as legal scientific articles, legal scientific papers, and theses and theses on AAUPB. The presentation of data in this paper uses qualitative techniques, where the data that has been obtained is described through narrative. The paper covers various aspects such as the definition and characteristics of abuse of authority, the relationship between abuse of authority and superior orders, and strategies that can be used to prevent abuse of authority. This study will provide readers with insights on the significance of understanding the concept of abuse of authority in the context of good governance. Additionally, the paper will suggest practical recommendations for local governments to reduce the risk of abuse of authority and promote good governance practices.